Field activity report: Thai Nguyen One Health field site implementation - Pham Thi Trang; Phan Thi Hong Phuc; Tran Nhat Thang; Sinh Dang-Xuan; Dang Thi Thuy Linh; Nguyen Le Thanh; Unger, Fred; Hung Nguyen-Viet (International Livestock Research Institute, 2025)
Northern Vietnam has been severely impacted by Typhoon Yagi, causing extensive destruction to livestock, particularly in Thai Nguyen and Quang Ninh. Prolonged flooding and widespread landslides have led to severe environmental pollution, creating favorable conditions for the proliferation of pathogens and vectors. This poses significant risks for outbreaks and the spread of animal diseases, increasing food safety concerns due to water pollution and contaminated food, which have severe implications for human, animal, and environmental health.